Hospitalization for ischemic stroke was affected more in independent cases than in dependent cases during the COVID-19 pandemic: An interrupted time series analysis. - Hiroyuki Nagano; Jung-Ho Shin; Tetsuji Morishita; Daisuke Takada; Susumu Kunisawa; Kiyohide Fushimi; Yuichi Imanaka (PLoS ONE)
Background The pandemic of the coronavirus disease 2019 (COVID-19) has affected health care systems globally. The aim of our study is to assess the impact of the COVID-19 pandemic on the number of hospital admissions for ischemic stroke by severity in Japan. Methods We analysed administrative (Diagnosis Procedure Combination-DPC) data for cases of inpatients aged 18 years and older who were diagnosed with ischemic stroke and admitted during the period April 1 2018 to June 27 2020. Levels of change of the weekly number of inpatient cases with ischemic stroke diagnosis after the declaration of state of emergency were assessed using interrupted time-series (ITS) analysis. The numbers of patients with various characteristics and treatment approaches were compared. We also performed an ITS analysis for each group ("independent" or "dependent") divided based on components of activities of daily living (ADL) and level of consciousness at hospital admission. Results A total of 170,294 cases in 567 hospitals were included. The ITS analysis showed a significant decrease in the weekly number of ischemic stroke cases hospitalized (estimated decrease: -156 cases; 95% confidence interval (CI): -209 to -104), which corresponds to -10.4% (95% CI: -13.6 to -7.1). The proportion of decline in the independent group (-21.3%; 95% CI: -26.0 to -16.2) was larger than that in the dependent group (-8.6%; 95% CI: -11.7 to -5.4). Conclusions Our results show a marked reduction in hospital admissions due to ischemic stroke after the declaration of the state of emergency for the COVID-19 pandemic. The independent cases were affected more in proportion than dependent cases.